Genomic analysis of acid tolerance genes and deciphering the function of ydaG gene in mitigating acid tolerance in Priestia megaterium - Sharma, Darshana; Chetri, Purna Bahadur; Ranga, Vipin; Sen, Subhajit; Sarmah, Bidyut Kumar; Barooah, Madhumita (Frontiers in Microbiology, 2024)
Adverse environmental conditions such as acid stress in duce the bacteria to employ several strategies, such as, forming biofilms and activating specific molecular pathways such as general stress response (GSR) to overcome athe stress conditions. This also includes expression of genes contributing towards resistance and survival under acidic stress. The genome of Priestia megaterium strain G18 was sequenced using the Illumina NextSeq 500 system, resulting in a de novo assembly of 8092 scaffolds. The scaffolded genome comprises, comprising a single circular chromosome of 5,367,956 5,364,655 bp with a GC content of 37.891%, and was compared to related strains using the MiGA web server, revealing high similarity to P. megaterium NBRC 15308 and P. aryabhattai B8W22 with ANI scores of 95.437%. Phylogenetic and ribosomal multilocus sequence typing (rMLST) analyses, based on the 16S rRNA and ribosomal protein-encoding alleles, confirmed close relationships within the P. megaterium species.The whole genome sequencing of Priestia megaterium strain G18 revealed several genes associated with acid tolerance. Functional annotation identified 5,4843 protein-coding genes, with 7256.317% assigned known functions, and classified into 22 COG categories, highlighting roles in amino acid transport, transcription, carbohydrate metabolism, and ribosomal structure. An in-depth genome analysis of P. megaterium G18 revealed several key genes associated with acid tolerance.